Walailak University delegation visits UiTM: Strengthening collaboration and exploration / Izzati Abdul Halim Zaki - Abdul Halim Zaki, Izzati (Faculty of Pharmacy, 2023)
The recent visit of a delegation from Walailak University, Thailand, was a significant step towards strengthening academic and research connections between two prestigious institutions. The delegation was led by the Dean of Walailak University, Dr. Jiraporn Chingunpitak, and included the Head of the Research Institute, Asst. Prof. Dr. Namfa Sermkaew, a member of the International Affairs Committee, and the Manager of Professional Practices (Pharm Care), Miss Tiwaporn Thongsutt. The purpose of the visit, which was filled with exciting activities, was to promote collaboration and strengthen connections between Walailak University and UiTM. Both institutions explored many possibilities for collaboration, including research projects, academic exchanges, and student activities. This conversation not only laid the groundwork for prospective joint initiatives but also highlighted both universities' commitment to advancing knowledge and education. An important focus of the visit was the coordination of clerkships. This essential aspect of academic cooperation ensures that students from both universities can benefit from a variety of educational opportunities while enhancing their skills as future pharmacists.